2005
DOI: 10.1016/j.eurpsy.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia calcification and psychosis in 22q11.2 deletion syndrome

Abstract: Intracerebral calcifications are a facultative symptom of hypoparathyreoidism in 22q11.2 deletion syndrome (22qDS). We describe a patient with 22qDS, basal ganglia calcification (BGC) and psychotic symptoms and discuss the etiological connection of BGC with psychiatric symptoms. Future work needs to determine the prevalence of BGC in 22qDS and psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“… 36 , 37 Cerebellar dysfunction has also been repeatedly observed in neurodevelopmental disorders, including ASD and ADHD. Other biological mechanisms that could be involved include striatal dysfunction, as increased volume of the striatum 38 40 and calcification of the basal ganglia 40 , 41 have been observed in 22q11.2DS. In addition, the 22q11.2 deletion is associated with early-onset Parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Cerebellar dysfunction has also been repeatedly observed in neurodevelopmental disorders, including ASD and ADHD. Other biological mechanisms that could be involved include striatal dysfunction, as increased volume of the striatum 38 40 and calcification of the basal ganglia 40 , 41 have been observed in 22q11.2DS. In addition, the 22q11.2 deletion is associated with early-onset Parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…Three generations (grandmother, mother and the patient) were diagnosed with FD. Sieberer et al (12) reported that risperidone remarkably improved the psychotic symptoms. Important features of dominant gene mutations are variable expression and reduce penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of thalamo- cortico-striatal circuitry leads to cognitive and affective dysfunction, and could manifest in schizophrenia-like psychosis. Sieberer et al (12) reported that risperidone remarkably improved the psychotic symptoms. Thus, it is recommended that psychotic symptoms associated with Far disease be treated with antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with longstanding hypoparathyroidism, there was evidence of generalized skeletal demineralization, vertebral crush fractures, osteoporosis and extensive bilateral symmetric calcification in brain tissue. Basal ganglia calcification is known to occur in patients with chronic hypocalcaemia, 1,2 but has been described rarely in patients with the 22q11.2 deletion syndrome 3,4 . The pathogenesis is incompletely understood but may be secondary to persistent hyperphosphataemia.…”
Section: Discussionmentioning
confidence: 99%
“…Basal ganglia calcification is known to occur in patients with chronic hypocalcaemia, 1,2 but has been described rarely in patients with the 22q11.2 deletion syndrome. 3,4 The pathogenesis is incompletely understood but may be secondary to persistent hyperphosphataemia.…”
Section: Discussionmentioning
confidence: 99%